2019
DOI: 10.1002/adma.201905751
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Locking Nanoparticles Disrupt the PD‐1/PD‐L1 Pathway for Efficient Cancer Immunotherapy

Abstract: The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated (Cas) enzyme, Cas13a, holds great promise in cancer treatment due to its potential for selective destruction of tumor cells via collateral effects after target recognition. However, these collateral effects do not specifically target tumor cells and may cause safety issues when administered systemically. Herein, a dual‐locking nanoparticle (DLNP) that can restrict CRISPR/Cas13a activation to tumor tissues is described. DLNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 39 publications
0
101
0
Order By: Relevance
“…Therefore, the antitumor effect of ITs depends on several factors: the affinity of Abs for TAA expressed on the cell surface, the rate of internalization of the complex, and the inherent efficacy and specificity of the toxin 25 . Immunotoxin‐based anti‐PD‐L1 mAb is considered to be an effective tumor treatment method in theory, because: (i) the immune checkpoint protein PD‐L1 is broadly expressed in many cancers, 9,20,26,27 which is spectral in treatment; (ii) its expression is limited in tumor area but not in normal cells, the treatment is mainly aimed at tumor tissue, which makes PD‐L1‐specific treatment more accurate, and its side‐effects limited; (iii) ELISA assay showed that PD‐L1, as a transmembrane protein, was not released from the constitutively expressing PD‐L1 cell membrane; and (iv) the key is that PD‐L1 on tumor cells is glycosylated, so when anti‐PD‐L1 mAb is combined in the glycosylated domain, it will produce internalization, 28 which provides a good antitumor basis for IT‐based treatment 28,29 . At present, PD‐L1‐specific treatment, such as PDL1‐Dox 30 and PD‐L1‐AuNP‐DOX 31 in the form of an Ab‐drug conjugate, have shown some promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antitumor effect of ITs depends on several factors: the affinity of Abs for TAA expressed on the cell surface, the rate of internalization of the complex, and the inherent efficacy and specificity of the toxin 25 . Immunotoxin‐based anti‐PD‐L1 mAb is considered to be an effective tumor treatment method in theory, because: (i) the immune checkpoint protein PD‐L1 is broadly expressed in many cancers, 9,20,26,27 which is spectral in treatment; (ii) its expression is limited in tumor area but not in normal cells, the treatment is mainly aimed at tumor tissue, which makes PD‐L1‐specific treatment more accurate, and its side‐effects limited; (iii) ELISA assay showed that PD‐L1, as a transmembrane protein, was not released from the constitutively expressing PD‐L1 cell membrane; and (iv) the key is that PD‐L1 on tumor cells is glycosylated, so when anti‐PD‐L1 mAb is combined in the glycosylated domain, it will produce internalization, 28 which provides a good antitumor basis for IT‐based treatment 28,29 . At present, PD‐L1‐specific treatment, such as PDL1‐Dox 30 and PD‐L1‐AuNP‐DOX 31 in the form of an Ab‐drug conjugate, have shown some promising results.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Polymer-based materials can simultaneously deliver agents with different hydrophilic and hydrophobic properties to enhance conventional therapies such as chemotherapy,p hotodynamic therapy (PDT), radiotherapy,a nd gene editing, highlighting their potential to induce immunogenic cell death and antitumor immunity. [12] Forinstance,F eng et al reported the use of alight-activatable prodrug of oxaliplatin, aphotosensitizer pheophorbide Ac ombined with an indoleamine 2,3-dioxygenase1 (IDO-1) inhibitor to efficiently elicit an immune response and to promote intratumor infiltration of cytotoxic Tlymphocytes. [12c] ICG-loaded PLGA nanospheres can enhance efficacy of CAR T-cell therapy by modulating the tumor microenvironment.…”
Section: Polymer-based Materialsmentioning
confidence: 99%
“…The results showed that DLNP successfully killed PD-L1 positive cancer cells, accurately regulated the activation of CRISPR/Cas13a, and further improved anti-tumor immunotherapy. [31] (Figure 3)…”
Section: Nano Drug Delivery Systemmentioning
confidence: 99%